(untitled) - Wootton, Robert J. (London, 1990)
Teleost fishes account for nearly half of all known vertebrate species. They have representatives in virtually all aquatic systems and an enormous variety in the ways they live. Moreover, teleost fishes support subsistence and commercial fisheries and aquaculture systems throughout the world.
Keywords: Fishes; Ecology